Risk factors and surgical approaches in neglected subaxial cervical spine fractures‐dislocations: Experiences with two cases and literature review - Ahmad Pour‐Rashidi; Bhavya Pahwa; Mohammad Hossein Khanmirzaie; Mahshid Fallahpour; Hamed Hanif; Mohammad Shirani (Clinical Case Reports, 2024)
Key Clinical Message This case report describes our experience of surgical strategies of two patients with neglected subaxial cervical spine fracture‐dislocation that came to our center with subsequent follow‐ups. Subaxial cervical spine fracture‐dislocation must be immediately diagnosed and treated. However, it can be neglected in some cases, especially in developing health care systems and patients with low socioeconomic status. We reported two neglected subaxial cervical fracture‐dislocation with a mean age of 54 years old who presented with axial cervical pain, and decreased muscle forces. In one out of two, cervical closed traction was applied, then unsuccessful result led to circumferential decompression and fixation via anterior–posterior (AP) approach. Accordingly, we used AP approach without applying closed reduction in another patient successfully. Except one of our cases who died after 2 weeks of surgery due to aspiration pneumonia, other one found complete improvement at the end of 6‐month follow‐up. Our study emphasizes the importance of AP approach in patients with irreducible joint dislocations. The approach can minimize the surgical risks and increase the cost–benefit as compared to three or more staged approaches. Our approach is less intensive than some other AP approaches while is a safe and efficacious procedure since the posterior reduction is not performed before discectomy and decompression.